Faktor-Faktor yang Mempengaruhi Share Repurchase Decisions Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Laras Gita Wulandari; Bahtiar Usman (Media Riset Bisnis & Manajemen, 2019)
AbstractPurpose –This study examines determinants of share repurchase decisions. The samples are obtained from the companies listed in Indonesian Stock Exchange (IDX) in the year of 2010-2017. The independent variables in this study acquisitions, depreciation, dividends, earning before interest and taxes, retained earnings, revenue, research and development, cash flow, and beta coefficient. The control variables in this study are long term debt to assets, debt to assets, and institutional ownership. The dependent variable is share repurchase decisions.Design/Methodology/Approach: The sample of this study included 18 (out of 555) in all sectors by using purposive sampling method. This study used panel regression analysis model for the empirical result. The study also found acquisitons, depreciation, dividends, retained earnings, long term debt to assets, and debt to assets had non-significant effect on share repurchase.The Finding - The results of the study revealed that earning before interest and taxes, revenue, research and development had a significant negative effect on share repurchase decisions and cash flow, beta coefficient, and institutional ownership had a significant positive effect on share repurchase decisions. A decrease in earnings before interest and tax expenses, research and development will encourage companies to share repurchase. To increase share repurchase, companies should increase in cash flow and pay attention that high systematic risk can increaseshare repurchase decisions.